Correlation of Body Mass Index with Endometrial Pathology in Perimenopausal Women with AUB: A Prospective Study - Saumya Bajpai Kaur; Sunmeet Singh; Amarjot Singh (Journal of Mid-Life Health)
Background: Body mass index (BMI) rises in correlation with endometrial cancer incidence as obesity rates among women have risen in recent years. In this study, we sought to evaluate the relationship between BMI and the perimenopausal ladies’ aberrant and normal endometrial pathology. We also evaluated the correlation of transvaginal ultrasonography findings with histopathological findings. Methodology: A prospective analytical study was conducted in a Tertiary care centre of Northern India over a period of 12 months from June 2022-May 2023 on women aged 40-55 years with Abnormal Uterine Bleeding (AUB) according to PALM-COEIN criteria. Patients were divided into two groups according to endometrial biopsy findings; women in group 1 were diagnosed with endometrial hyperplasia or carcinoma, while women in group 2 had normal endometrium, according to WHO classification. BMI, Endometrial biopsy pathology and transvaginal ultrasonography findings were noted. Data was analysed using SPSS version 24.0. Results: Out of 72 patients, 22 patients had histopathological findings of Adenocarcinoma (3, 13.6%) and endometrial hyperplasia (19, 86.4%) and rest 50 patients had normal proliferative (13, 26%). On the basis of BMI, 51.5% (32/72) were overweight, 31.9% (23/72) were of Normal BMI, 11.1% (15/72) were Obese. The mean age in Group A and B was 52.37 ± 2.68 and 48.74 ± 7.98 respectively (P value- 0.003). Significant association between obesity and endometrial hyperplasia or carcinoma (P value-0.033). Correlation of Transvaginal Ultrasound (TVS) findings with that of histopathology was statistically significant (P value-0.002). Adenomyosis and Polyp and 100% correlation percentage on TVS and Histopathology. Conclusion: There is a direct link between a high body mass index and AUB due to endometrial hyperplasia. Importance of physical activity as a preventative factor against AUB, endometrial cancer, and hyperplasia should be promoted. TVS is also a suitable diagnostic technique for the assessment of AUB as an initial procedure.